Perceived unfairness in CEO compensation and work morale - Thomas Cornelissen; Oliver Himmler; Tobias Koenig (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
CEO compensation that is perceived to be excessive regularly causes agitation in the population. Using German data, we show that perceiving CEO pay to be unjust has economic repercussions in terms of lower work morale.
Keywords: A13; D63; J22; 330; Fairness; Social Comparisons; Work Morale; Führungskräfte; Gehalt; Wahrnehmung; Soziale Gerechtigkeit; Arbeitsethik; Deutschland